Chapter The Old Serbian Version of the Antiochene Recension of Samuel-Kings: Some Preliminary Issues in Textual Criticism - BRUNI, Alessandro Maria (Biblioteca di Studi Slavistici, 2018)
The article discusses several textual features of the second Church Slavonic version of 1-4 Kingdoms, which has come down to us in two manuscripts, written in Serbian Resavian orthography. The earliest copy dates from 1418 (National Research Library of Odessa, no. 6 [1/106]), while the second is from 1523-1543 (Moscow, Russian State Library, f. 87 N° 1 [1684]). The paper presents this tradition to scholars as new material for the study of the Antiochene or Lucianic recension of 1-4 Kingdoms, a text-type found in five Greek manuscripts. The analysis shows that it represents a new witness, not only to the Antiochene recension of 1-4 Kingdoms as a whole, but also to its proto-Lucianic textual stratum.